Characterization and in vitro digestion of alkali-extracted polysaccharides from Grifola frondosa and its impacts on human gut microbiota - Tian, Baoming; Zhou, Xue; Geng, Yan; Hu, Jiangning; Ye, Bangwei; Sun, Peilong; Yang, Kai (Food bioscience, 2024)
Grifola frondosa is a highly valued, edible and biologically active fungus in which the polysaccharide component plays a major role. To investigate the fundamental structure, in vitro digestion and fermentation characteristics of Grifola frondosa polysaccharides (GFP), GFP from the waste residue of Grifola frondosa after water extraction was re-extracted by alkaline solution. The carbohydrate and β-glucan contents of GFP were 91.61% and 60.57%, respectively, and were mainly composed of glucose. GFP can form triple supercoils and combine with Congo red, and the surface of GFP was smooth and dense, and the particles were in the shape of long column, sheet and ellipse. Analysis of carbohydrate, reducing sugars, and further chromatogram data also showed that GFP was not degraded by the simulated digestion process of the mouth, stomach and small intestine. Fecal fermentation of GFP significantly increased the abundance of Bacteroidota, and decreased Proteobacterias in both normal weight and obese subjects in vitro. The short-chain fatty acid (SCFA)-producing bacteria, Faecalibacterium, Erysipelotrichaceae_UCG_003, Lactococcus were increased, and Dorea and Escherichia-Shigella were reduced after GFP treatment. Thus, the molecular of GFP was utilized and degraded by the gut microbiota and metabolized into SCFAs. This decreased pH, H2S, and NH3, as well as increased CO2 in the fermentation broth. In conclusion, GFP can modulate the composition of the gut microbiota and is a potentially functional product. [Display omitted] •Grifola frondosa polysaccharides (GFP) were extracted and investigated.•The carbohydrate and β-glucan contents of GFP were 91.61% and 60.57%.•GFP plays beneficial roles in regulating gut flora in healthy and overweight people.•GFP can promote the production of SCFAs by increasing SCFA-producing bacteria.•GFP can be developed as a prebiotic in functional foods to regulate gut microbiota.